The Supremacy of Revelation over Reason: Al-Ghazali's Critique of Rationalist Philosophy in Tahafut Al-Falasifah - Mujahidin, Sultan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study examines the implications of the supremacy of revelation over reason in the development of Islamic philosophical thought, with a specific focus on Al-Ghazali’s Tahafut al-Falasifah. It seeks to address three key questions: (1) How does Al-Ghazali conceptualize the relationship between reason and revelation in the acquisition of knowledge? (2) What socio-cultural, political, and intellectual factors influenced Al-Ghazali’s critique of rationalist philosophy and his prioritization of revelation? (3) What are the broader implications of his thought for the evolution of Islamic theology and philosophy after the publication of Tahafut al-Falasifah? Using a descriptive-analytical approach, this study explores Al-Ghazali’s arguments within the context of broader Islamic philosophical debates, emphasizing his assertion of revelation as the ultimate epistemological authority. The findings indicate that Al-Ghazali viewed divine revelation as the most reliable and authoritative foundation for knowledge, challenging the dominance of Peripatetic Islamic philosophy, which heavily relied on Greek rationalist traditions. His critique was shaped by the socio-political milieu of his time, marked by the increasing popularity of rationalist philosophy and its perceived threat to Sunni orthodoxy. The study concludes that Al-Ghazali’s prioritization of revelation resulted in a gradual decline in critical reasoning and fostered greater skepticism toward foreign ideas within Islamic intellectual traditions. These developments significantly shaped theological and philosophical trajectories in the post-Tahafut era, highlighting the enduring impact of Al-Ghazali’s thought on Islamic intellectual history.